2001
DOI: 10.1111/1467-8624.00332
|View full text |Cite
|
Sign up to set email alerts
|

Mother – Child Conversational Interactions as Events Unfold: Linkages to Subsequent Remembering

Abstract: The study reported here was designed to examine linkages between mother-child conversational interactions during events and children's subsequent recall of these activities. In this longitudinal investigation, 21 mother-child dyads were observed while they engaged in specially constructed activities when the children were 30, 36, and 42 months of age. Analyses of the children's 1-day and 3-week recall of these events indicated that at all age points, features of the activities that were jointly handled and joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
114
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 27 publications
16
114
1
Order By: Relevance
“…Thirty-eight mother-child dyads (DS = 18; TD = 20) completed the protocol for younger children, and 32 dyads (DS = 16; TD = 16) completed the protocol for older children. Mothers of children at younger levels were first provided with picnic-themed toys and asked to go on a pretend picnic with their child, based on task used by Haden et al (2001) for TD children ages 30 to 42 months and their mothers. The dyad was then provided with three boxes (one with drawing and coloring materials, one with a cash register and dress-up clothes, and one with blocks) and instructed to play for about 15 min, spending as long as they desired with the items in each box.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-eight mother-child dyads (DS = 18; TD = 20) completed the protocol for younger children, and 32 dyads (DS = 16; TD = 16) completed the protocol for older children. Mothers of children at younger levels were first provided with picnic-themed toys and asked to go on a pretend picnic with their child, based on task used by Haden et al (2001) for TD children ages 30 to 42 months and their mothers. The dyad was then provided with three boxes (one with drawing and coloring materials, one with a cash register and dress-up clothes, and one with blocks) and instructed to play for about 15 min, spending as long as they desired with the items in each box.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, 15- Why do verbal cues facilitate the memory abilities of young infants? Elaborative verbal information can serve to highlight which aspects of an event are important and interesting to recall, which in turn influences the content, quality, and organization of the child's subsequent verbal report (e.g., Haden et al, 2001;McGuigan & Salmon, 2004;Tessler & Nelson, 1994). It is possible that verbal information may have the same impact on the structure and organization of non-verbal recall.…”
Section: Language Cues and Imitation Page 4 Of 11mentioning
confidence: 99%
“…Preschool children's verbal reports of previous experiences are influenced by their language abilities at the time of the event (Simcock & Hayne, 2002) as well as the discussions they have during or after the event (e.g., Haden, Ornstein, Eckerman, & Didow, 2001;McGuigan & Salmon, 2004Tessler & Nelson, 1994). For example, elaborative talk (compared to empty, uninformative talk) by an experimenter during the event facilitates 3-to 5-year olds verbal recall two weeks after participating in a staged novel event (McGuigan & Salmon, 2004).…”
mentioning
confidence: 99%
“…Children play an active role in this process of memory development. Research has shown that children's memory for an event is better when the event is talked about by the child and another person, such as the mother, than when the event is only talked about by another person or not discussed (Haden, Ornstein, Eckerman, & Didow, 2001). Research has also demonstrated that children use memory strategies in conversation with an unfamiliar adult similar to what was previously used with their mothers (Lange & Carroll, 2003), suggesting that parent-child conversation has implications for when children remember events on their own.…”
Section: Three Current Research Directionsmentioning
confidence: 99%